Perbandingan rencana strategis perbankan daerah dengan analisis SWOT - Lailiyah, Hasanatul; Kamalia, Isna; Sistha, Adinda Mutiara Widya (Maliki Interdisciplinary Journal, 2024)
The purpose of this study was to determine the comparison of strategic plans at Bank Jatim, Bank BJB, and Bank Jombang using SWOT analysis. This research was conducted using descriptive qualitative methods with literature study and document study techniques. The data used is secondary data. The results showed that SWOT analysis helps banks gain an advantage over their competitors by providing an in-depth understanding of strengths, weaknesses, opportunities, and threats (SWOT). The three financial institutions have their own strengths, weaknesses, opportunities, and threats. The strategy plan for each bank will be different based on the bank’s circumstances.